Measurement of Crosslinked Fibrin Derivatives -Use in the Diagnosis of Venous Thrombosis - Rowbotham, Beverley J; Carroll, Patrick; Whitaker, Alan N; Bunce, Ian H; Cobcroft, Ralph G; Elms, Mervyn J; Masci, Paul P; Bundesen, Peter G; Rylatt, Denis B; Webber, Anthony J (Thrombosis and Haemostasis, 1987)
The measurement of crosslinked fibrin derivatives in plasma has received evaluation as a screening test in the diagnosis of venous thrombosis. Plasma samples were taken from 104 patients undergoing venography because of clinical suspicion of lower limb venous thrombosis. The samples were assayed using a monoclonal antibody identifying an epitope on D dimer and larger crosslinked fibrin derivatives in an enzyme immunoassay. 100% of patients with positive venograms had elevated levels of these molecules. While a percentage of patients with negative venograms also had increased levels, alternative clinical explanations were apparent in most. A normal D dimer value excludes the diagnosis of venous thrombosis, while an increased value supports it. The measurement of crosslinked fibrin derivatives in plasma may play a role in the selection of patients for venography.
Keywords: Venous thrombosis; D dimer; Fibrin crosslinking; monoclonal antibodies